Impacts of Covid-19 Pandemic on Ecotourism Segment in Amazonas State, Brazil - Vidal, Marcelo Derzi; Pozzan Paim, Fernanda; Meloni Nassar, Pedro; Rodrigues Simonetti, Susy (Anais Brasileiros de Estudos Turísticos, 2021)
The COVID-19 pandemic has affected tourism worldwide. This paper examines the impacts of pandemic on companies and professionals related to ecotourism in the state of Amazonas, Brazil. For this purpose, we sent online structured questionnaire to workers in the sector, whose participation was voluntary and anonymous. We had 44 responses from seven macro-regions in the state, most of which were guides and workers in the market for over 15 years. For 91% of respondents, the pandemic totally affected personal or company turnover. Strategies to minimize impacts were adopted in 97% of cases, such as cancellation or rescheduling. The turnover forecast for the remainder of 2020 was very high for 38.6% of respondents. The budget recovery forecast is of at least two years for 43.2% of the cases. The professionals related to ecotourism in Amazonas had their activities affected and the perspective is for a slow recovery, resulting in vulnerability for the activity. Brazil's current image abroad, referring to the weak implementation of actions to mitigate the effects of the pandemic, represents a risk to the activity in Amazonas. Public policies are of utmost importance to recover the ecotourism and the valorization of the different actors and companies related to this tourist segment. Keywords: Amazon; Coronavirus; Social isolation; Protected area; Tourism.